Theoretical Analysis of a 2D Metallic/Semiconducting Transition‐Metal Dichalcogenide NbS2//WSe2 Hybrid Interface. Issue 12 (27th October 2020) - Golsanamlou, Zahra; Sementa, Luca; Cusati, Teresa; Iannaccone, Giuseppe; Fortunelli, Alessandro
Abstract: A first‐principles theoretical study of a monolayer‐thick lateral heterostructure (LH) joining two different transition metal dichalcogenides, NbS2 and WSe2, is reported. The NbS2 //WSe2 LH can be considered a prototypical example of a metal (NbS2 )/semiconductor (WSe2 ) 2D hybrid heterojunction. First, realistic atomistic models of the NbS2 //WSe2 LH are generated and validated, its band structure is derived, and it is subjected to a fragment decomposition and electrostatic potential analysis to extract a simple but quantitative model of this interfacial system. Stoichiometric fluctuations models are also investigated and found not to alter the qualitative picture. Then, electron transport simulations are conducted and they are analyzed via band alignment analysis. It is concluded that the NbS2 //WSe2 LH appears as a robust seamless in‐plane 2D modular junction for potential use in optoelectronic devices going beyond the present miniaturization technology. Abstract : A 2D lateral heterostructure (LH) between two different transition metal dichalcogenides, NbS2 //WSe2, is investigated as a paradigmatic conducting/semiconducting 2D hybrid heterojunction via first‐principles calculations. Electrostatic potential and fragment analyses together with transmission simulations demonstrate that NbS2 //WSe2 LH is robust and very promising in‐plane 2D modular junction for potential use in optoelectronic devices going beyond the present miniaturization technology.